2020
DOI: 10.1145/3446243.3446250
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence for students in postsecondary education

Abstract: AI-based apps can facilitate learning for all post-secondary students and may also be useful for students with disabilities. Here we share some reflections from discussions that took place during two advisory board meetings on the use of such apps for students with disabilities at the post-secondary level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…An Artificial Intelligence Advisory Board (Adaptech Research Network, 2020) consisting of an international team of consumers, scholars, and researchers indicated that the literature on the issue, though of apparent interest and timeliness, is rather sparse and predominantly descriptive (e.g., Martiniello et al, 2020) and that there is little consensus among stakeholders about how to define AI and AI-enabled functionality to facilitate learning. Consequently, our systematic search strategy was built around the explicit use of the key term "artificial intelligence," supplemented by indications of relevant educational purposes, settings, environments, and categories of learners.…”
Section: Collating Summarizing and Reporting The Resultsmentioning
confidence: 99%
“…An Artificial Intelligence Advisory Board (Adaptech Research Network, 2020) consisting of an international team of consumers, scholars, and researchers indicated that the literature on the issue, though of apparent interest and timeliness, is rather sparse and predominantly descriptive (e.g., Martiniello et al, 2020) and that there is little consensus among stakeholders about how to define AI and AI-enabled functionality to facilitate learning. Consequently, our systematic search strategy was built around the explicit use of the key term "artificial intelligence," supplemented by indications of relevant educational purposes, settings, environments, and categories of learners.…”
Section: Collating Summarizing and Reporting The Resultsmentioning
confidence: 99%
“…Various sectors, such as the educational sector, have implemented AI virtual assistants for advanced and higher education (Page & Gehlbach, 2017;Zawacki-Richter et al, 2019). This rapid development brings convenient daily life to students, especially for learners with disabilities, specifically the visually impaired ones (Forbes & Lasonen, 2021;Martiniello et al, 2021). Learners with visual impairments may be blind, partly sighted, or have poor vision.…”
Section: Introductionmentioning
confidence: 99%
“…Various sectors, such as the educational sector, have implemented AI virtual assistants for advanced and higher education (Hamuddin et al, 2020;Villegas-Ch et al, 2020;Zawacki-Richter et al, 2019). This rapid development brings convenient daily life to students, especially for learners with disabilities, specifically the visually impaired ones (Forbes & Lasonen, 2021;Martiniello et al, 2021). Learners with visual impairments may be blind, partly sighted, or have poor vision.…”
Section: Introductionmentioning
confidence: 99%